Raton class of 1952 reunites (Raton Range Raton, New Mexico, 1977)
Newspaper Article on the class of 1952 and their 25th Class Reunion.
Master list item #: 4
File location is in the Raton File Cabinet
Keywords: Jones, Caroly Colbert; Pappas, Mike; Davis, Oliver; Keeler, Curtis; LaBlanc, Line; Smedly, Charles W. Jr; Oldham, Dorothy; Thomson, Frank; Atchison, Marvel; Troy, Helen; Durham, Hazel Sever; Modrich, Larry; Segotta, Donald; Webb, Sue Coots; Mileta, Pete; Bandy, Jim; Raton High School; Elks Club; Local History; Biography; Life and Customs; Class Reunions; Celebration; Raton, New Mexico; New York; Colorado; California; Alabama; Texas; Washington